Ethos und Pathos der Geisteswissenschaften: Konfigurationen der wissenschaftlichen Persona seit 1750 - Werle, Dirk; Klausnitzer, Ralf (Historia Hermeneutica / Series Studia, 2015)
This book examines the ways that texts from the humanities have fostered particular approaches to knowledge by constructing different versions of a 'scientific ethos'. The studies contained in this volume reveal how and why different forms of scientific ethos have developed since the mid-18thcentury. The studies also illuminate associated styles of rhetorical argumentation. Ralf Klausnitzer, Carlos Spoerhase and Dirk Werle, Humboldt University Berlin, Germany.